2007
DOI: 10.1523/jneurosci.4866-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Specific Alterations of T-Type Calcium Current in Painful Diabetic Neuropathy Enhance Excitability of Sensory Neurons

Abstract: Recent data indicate that T-type

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
218
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 240 publications
(243 citation statements)
references
References 63 publications
17
218
2
2
Order By: Relevance
“…Previous studies demonstrated the existence of T-type Ca 2+ currents in cultured rat DRG neurons [9,28,53]. Under our experimental conditions (10 mM external Ca 2+ ) we could identify cells showing no T-type currents, cells with T-type smaller than HVA currents and cells with Ttype larger than HVA currents.…”
Section: Trpv1 and T-type Channels In Drg Neuronsmentioning
confidence: 49%
See 4 more Smart Citations
“…Previous studies demonstrated the existence of T-type Ca 2+ currents in cultured rat DRG neurons [9,28,53]. Under our experimental conditions (10 mM external Ca 2+ ) we could identify cells showing no T-type currents, cells with T-type smaller than HVA currents and cells with Ttype larger than HVA currents.…”
Section: Trpv1 and T-type Channels In Drg Neuronsmentioning
confidence: 49%
“…As T-type channels at the DRG somatic level are known to play a key role in the control of sensory neuron excitability in both physiological conditions [45,66,71] and pain states [28,29], the TRPV1-mediated inhibition of T-type channels reported here has potential overall consequences on nociceptive signals induction and transmission [18,30,31].…”
Section: Trpv1 and T-type Channel Coupling Is Camentioning
confidence: 82%
See 3 more Smart Citations